Just do 30 and 22 by multiplication Step-by-step explanation:
Answer: C. Subtraction Property of Inequality
Answer:
1.
Step-by-step explanation:
1. 2x-4=10
2x=14
x=7
2. 3x+3=2x-1
3x-2x=-1-3
x=-4
3. 7x+x=24
8x=24
x=3(
4. 5+x=-18
x=-18-5
x=-23
5. -14=10-6x
6x=10+14
6x=24
x=4
6. 2x-2=x+12
2x-x=12+2
x=14
7. 3x-31=2
3x=2+31
3x=33
x=11
8. 5x-14=16
5x=16+14
5x=30
x=6
9. 2x+8=4(5-x)
2x+8=20-4x
2x+4x=20-8
6x=12
x=2
10. 2x-3=3(1+x)
2x-3=3+3x
2x-3x=3+3
-x=6
Answer:
3) f(x) = 3(x + 2)^2 - 1.
Step-by-step explanation:
f(x) = 3x² + 12x +11
f(x) = 3(x^2 + 4x) + 11 Completing the square:
f(x) = 3[(x + 2)^2 - 4] + 11
f(x) = 3(x + 2)^2 -+3*-4 + 11
f(x) = 3(x + 2)^2 - 12 + 11
f(x) = 3(x + 2)^2 - 1.